Social anxiety in 18 nations: sex and age differences (2008)
The aim of this study was to examine age and sex differences in 6 dimensions of social anxiety in a sample of 16,940 people over the age of 16 in 18 countries in Ibero-America. Participants completed the 'Social Anxiety Questionnaire for Adults' (SAQ-A), which includes the following dimensions: 1. Awkward behavior in socially embarrassing situations; 2. Interactions with the opposite sex; 3. Interactions with strangers; 4. Criticism and embarrassment; 5. Assertive expression of annoyance, disgust or displeasure; and 6. Speaking/performing in public/Talking with people in authority. The results showed that women reported significantly more anxiety than men in 88.67% of the social situations covered by the SAQ-A. All but three countries showed significant sex differences in social anxiety with women reporting greater anxiety than men. With regards to age, the younger age groups (up to the age of 24) showed greater sex differences in social anxiety depending on the specific social anxiety dimensions. Finally, anxiety and age was positively associated for some social anxiety dimensions and negatively or U-shaped for others. Although the sample size was very large, some of the results will require future replication. (PsycINFO Database Record (c) 2016 APA, all rights reserved)